Concepts of education and counseling based on Paulo Freire - Delima, Delima; Marsidin, Sufyarma (Counseling and Humanities Review, 2022)
Educational practices so far have emphasized left-brain developments that tend to think rigidly, structured, bound by formal rules, and very formalistic. As a result, all educational processes must be carried out according to a straight line determined by the holders and policymakers who are poor in creativity and innovation. Humans are actors or subjects. The vocation of a true human being is to be a conscious actor, who acts over the world and reality with a critical and creative attitude. In the cognitive realm, it has always been the foundation for measuring the level of success of the educational process. Even though the set of rules has demanded a balance of the three domains (cognitive, affective, and psychomotor) and even the spiritual realm, reality is far from expectations. The limitations of the competency skills of educators have always been endless reason. Various aspects of education: the characteristics of students, identifying cases, inhibiting and supporting factors in the implementation of education, and counseling guidance, this is what Paulo Freire offers to be an alternative development in the world of education.